ESTIMATION OF SITE RESPONSE CHARACTERISTICS AT FOUR SITES OF SEISMIC MONITORING NETWORK IN PAKISTAN - Ahmed, S.; Shah, M. D.; Qaisar, M.; Khan, K. (The Nucleus, 2020)
The widely used approach proposed by Nakamura was adopted for the assessment of site response characteristic parameters namely; resonance frequency and amplification factor that are important for seismic hazard assessment and yield assessment in case of explosions. The technique involves calculation of spectral ratios of the horizontal to vertical components (H/V) of ambient noise recorded at sites of seismic monitoring network. The resonant frequency and amplification factor for four selected sites were estimated. The ambient noise at these sites have ground amplification factor of 1.2 – 3.75 over the frequency range of 1.05 – 4.90 Hz. The normalized spectral ratio reflects the dominant frequency and relative amplification of the selected sites. The amplification factors estimated for Sakesar and Fatehjang sites are higher than Nilore and Nurpur sites. These results are fully supported by the fact that calculated magnitudes of seismic events (local, regional and teleseismic) recorded at Sakesar and Fatehjang show higher values as compared to Nilore and Nurpur sites.